Kedudukan Kesepakatan Para Pihak dalam Transaksi Jual Beli Tanah Hak milik Perseorangan - Tuti Handayani; Joni Irawan; Nikolen Tipagau (Universitas Sains dan Teknologi Komputer, 2024)
The aim of this research is to provide information to every actor buying and selling land regarding the binding agreement between the parties regarding the price and land used as the object of sale and purchase and to provide information to each actor buying and selling land regarding the rights and obligations inherent after the price and land used as the object of sale and purchase are agreed upon. This research uses a qualitative approach, researchers not only collect data in terms of quality, but also want to gain a deeper understanding behind the phenomena obtained. This is because qualitative research has a close relationship with social reality and human behavior. The qualitative approach aims to explore or build a proposition or explain the meaning behind reality. The word agreement or agreement as one of the conditions regulated, determined and contained in Article 1320 which is realized and created by the Seller and the Buyer in the sale and purchase of privately owned land, is not carried out at random, but must fulfill the conditions, one of which is regulated, determined and contained in Article 1321 of the Civil Code. Must fulfill the elements.